High energy density in artificial heterostructures through relaxation time modulation - Han, Sangmoon; Kim, Justin S.; Park, Eugene; Meng, Yuan; Xu, Zhihao; Foucher, Alexandre C.; Jung, Gwan Yeong; Roh, Ilpyo; Lee, Sangho; Kim, Sun Ok; Moon, Ji Yun; Kim, Seung Il; et al. (Science, 2024)
Electrostatic capacitors are foundational components of advanced electronics and high-power electrical systems owing to their ultrafast charging-discharging capability. Ferroelectric materials offer high maximum polarization, but high remnant polarization has hindered their effective deployment in energy storage applications. Previous methodologies have encountered problems because of the deteriorated crystallinity of the ferroelectric materials. We introduce an approach to control the relaxation time using two-dimensional (2D) materials while minimizing energy loss by using 2D/3D/2D heterostructures and preserving the crystallinity of ferroelectric 3D materials. Using this approach, we were able to achieve an energy density of 191.7 joules per cubic centimeter with an efficiency greater than 90%. This precise control over relaxation time holds promise for a wide array of applications and has the potential to accelerate the development of highly efficient energy storage systems.